Food system environmental data layers compiled and adapted to further innovate the Food Systems Dashboard - CGIAR Research Program on Water, Land and Ecosystems (2020)
Food Systems Dashboard with integrated environmental layers as decision-support tool is available online and linked to support UN Food Systems Summit processes.